Metabolic syndrome and its components are associated with increased chronic kidney disease risk: Evidence from a meta‐analysis on 11 109 003 participants from 66 studies. Issue 8 (23rd May 2018) - Alizadeh, Shahab; Ahmadi, Mahsa; Ghorbani Nejad, Behnam; Djazayeri, Abolghassem; Shab‐Bidar, Sakineh
Summary: Background & aims: Observational studies examining the relationship between metabolic syndrome and the risk of chronic kidney disease (CKD) have reported inconclusive results. This meta‐analysis was performed to resolve these controversies. Methods: The MEDLINE, EMBASE, and PubMed databases were systematically searched from their inception until March 2016 to identify all relevant studies. Risk estimates and their corresponding 95% confidence intervals (CIs) for the associations of MetS and its components with CKD risk were extracted and pooled using a random‐effects model. Results: A total of 66 studies, including 18 prospective cohorts and 48 cross‐sectional studies, with 699 065 CKD patients and 11 109 003 participants were included in the meta‐analysis. When all definitions were pooled, the presence of MetS was associated with a significant 50% increase of CKD risk (OR = 1.50, 95% CI = 1.43‐1.56), with evidence of moderate heterogeneity ( I 2  = 72.3%, P  < .001). The risk of CKD associated with MetS was higher in studies using the American Heart Association/National Heart, Lung, and Blood Institute criteria (OR = 1.68, 95% CI = 1.25‐2.10) compared with those using the Adult Treatment Panel III (OR = 1.49, 95% CI = 1.42‐1.56) and the International Diabetes Federation (OR = 1.32, 95% CI = 1.22‐1.41) definitions. This relationship was independent of diabetes status. Moreover, all individual components of the MetS were significantly associated with CKD, and their coexistence resulted in an escalating dose‐response relationship. The sensitivity and subgroup analyses established the stability of the findings. Conclusions: This meta‐analysis strongly suggests that the metabolic syndrome and its components are independently associated with the increased risk of CKD.